Analysis of cost-effectiveness in the provision of air navigation services at functional air blocks. Issue 4 (December 2019) - Ansuategi, Alberto; Galarraga, Ibon; Orea, Luis; Standfuss, Thomas
The Single European Sky (SES) legislation is intended to have a major impact on the fragmentation in the European Air Traffic Management and Communications, Navigation and Surveillance (ATM/CNS) system. A fundamental aspect of the SES initiative is functional airspace blocks (FABs), which have the goal of reducing the inefficiencies—in terms of safety, capacity, and cost—that result from the fragmentation of European airspace. FABs are seen as an explicit bottom-up first step toward the ultimate integration of European airspace. In this article, we focus on the analysis of the evolution of the cost-effectiveness in the provision of ATM/CNS services at FABs. We proceed in two stages. First, we develop a theoretical framework that allows us to decompose the change in cost-effectiveness of FABs into its basic sources. Second, we use stochastic frontier analysis techniques to estimate the cost equations and decompose the change in the cost-effectiveness of the nine European FABs into several components. Our analysis sheds light on (1) the drivers of changes in the air navigation service providers (ANSPs) and FABs cost-effectiveness from 2006 to 2016, (2) the role that FABs play in enhancing cooperation between ANSPs to obtain operational efficiency gains, and (3) the existence of economies of scale in the European ATM/CNS service provision.